2019
DOI: 10.1038/s41545-019-0044-z
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-based polymer nanocomposite membranes for oily wastewater treatment

Abstract: Increasing oil contaminants in water is one of the major environmental concerns due to negative impacts on human health and aquatic and terrestrial ecosystems. The objective of this review paper is to highlight recent advances in the application carbon-based polymer nanocomposite membranes for oily wastewater treatment. Carbon-based nanomaterials, including graphene and graphene-oxide (GO), carbon nanotubes (CNTs), and carbon nanofibers (CNFs), have gained tremendous attention due to their unique physicochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(41 citation statements)
references
References 99 publications
0
41
0
Order By: Relevance
“…Application of carbon nanofibrous films in oily/water treatments is advantageous over organic polymer-based sorbents for being stable in harsh conditions (acidic or basic media). However, very few studies have been reported on fabrication of carbon nanofibers for oily water treatments [ 135 ]. A pioneering work using electrospun nanofibers conducted by Liu et al, introduced a flexible and recyclable electrospun carbon nanofibrous film for oil-water separation (water contact angle of 155.3°, oil uptake capability of 138.4 g/g −1 for silicone oil) [ 136 ].…”
Section: Environmental Applicationmentioning
confidence: 99%
“…Application of carbon nanofibrous films in oily/water treatments is advantageous over organic polymer-based sorbents for being stable in harsh conditions (acidic or basic media). However, very few studies have been reported on fabrication of carbon nanofibers for oily water treatments [ 135 ]. A pioneering work using electrospun nanofibers conducted by Liu et al, introduced a flexible and recyclable electrospun carbon nanofibrous film for oil-water separation (water contact angle of 155.3°, oil uptake capability of 138.4 g/g −1 for silicone oil) [ 136 ].…”
Section: Environmental Applicationmentioning
confidence: 99%
“…However, with the rising concerns on the toxicity of silver (Ag) entrainment into biological systems and the environment it has become necessary for further research on silver-nanoparticles toxicology impact assessment when they coexist with or without their bioavailable ions [74,75]. Noamani et al [70] reviewed the extensive studies that have been carried out on carbon-based polymer nanocomposite membranes for oily wastewater treatment. They reported that incorporating materials such as carbon-nanotubes (CNTs), graphene, graphene-oxide (GO), and carbonnanofibers (CNFs) into polymeric membranes, enhanced the performance output of such membrane systems in terms of permeations, antifouling, and self-cleaning characteristics.…”
Section: Membranesmentioning
confidence: 99%
“…This study argued that there was an increase in the hydrophilicity of the PES hollow fiber UF membranes when hydrophilic functionalized graphene was Fig. 4 An overview of the optimization of conventional polymeric membranes by nano-doping for improved functionality, cost implications, and smaller environmental footprints [34,70] grafted to G-PANCMI or ultra-wetting graphene, which was successful in the separation of the oil-water mixture, hence presenting the possibility of mitigating the challenges of using polymeric membranes for oil-water separation. Similarly, Liu et al [78] developed a novel antifouling ultralight free-standing reduced GO membrane for oil-in-water emulsion separation.…”
Section: Membranesmentioning
confidence: 99%
“…Carbon-based polymer nanocomposites are versatile materials for a number of purposes such as environmental and energy applications [ 1 , 2 , 3 ]. This is mainly due to the unique properties of carbon-based nanomaterials (such as graphene-based materials) which exhibit high electrical and thermal conductivities, excellent mechanical properties, and light weight [ 4 ].…”
Section: Introductionmentioning
confidence: 99%